2017
DOI: 10.1002/jsfa.8344
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dehydration methods on quality characteristics of yellow passion fruit co‐products

Abstract: This study reinforces the importance of the adequate use of passion fruit co-products due to the high levels of bioactive compounds in this material. Microwave dehydration presented the best results, which indicates the potential use of this technique for a better exploitation of fruit co-products. Larger quantities of pectin were extracted from samples dehydrated through methodologies with long-time process and low temperatures, such as convective drying and freeze-drying. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…It is also observed that there is no statistical difference between r-YPFs and o-YPFs regarding these contents ( p > 0.05). Such composition of YPF agrees with earlier reports. ,, …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…It is also observed that there is no statistical difference between r-YPFs and o-YPFs regarding these contents ( p > 0.05). Such composition of YPF agrees with earlier reports. ,, …”
Section: Resultssupporting
confidence: 93%
“…Such composition of YPF agrees with earlier reports. 2,8,29 The compositional data shown in Table 1 indicate that the proportions of rind in r-YPFs and o-YPFs are similar. Rind and pulp of YPFs were specifically used to obtain edible films by continuous casting.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…According to Mohandas et al [ 39 ] and Maidana et al [ 6 ], pectinase activity tends to be significantly higher when the microorganism grows in pectin added medium, in comparison to simple sugars. The passion fruit peel shows a pectin content of around 400 mg g −1 of dry matter [ 15 ], a high content in comparison to other food residues as reported by Müller-Maatsch et al [ 40 ]. Besides the pectin content, the passion fruit peel flour can reach amounts of ash, proteins, fat, and other carbohydrates of 7.5, 4.8, 0.9, and 23.4% w / w (dry basis) respectively, according to Duarte et al [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over 40% of the production is destined to the juice industry and around 50% of the fruits total mass is discarded as peel, which may be dried, ground and marketed as a flour PFRF [ 13 , 14 ]. Passion fruit peel shows a pectin content of around 7 g 100 g −1 , considerably higher than apple, persimmon, beet pulp, orange, strawberry, tomato, and grape, of which agro-industrial residues contain between 0.2 and 4 g 100 g −1 of pectin [ 15 ].…”
Section: Introductionmentioning
confidence: 99%